The Development of entrepreneurship in students technology based university of Lancang Kuning Pekanbaru - Tanjung, Abrar; Ambiyar, Ambiyar; Verawardina, Unung; Adri, Junil; Efrianova, Vivi; Ferdiansyah, Ferdiansyah; Prima, Fani Keprila (Jurnal Pendidikan Teknologi Kejuruan, 2020)
Technopreneur, one part of the development of entrepreneurship (entrepreneur), provides a picture of entrepreneurship using technology-based innovation. The technopreneur concept is based on a technology base that is used as an entrepreneurial tool, for example the emergence of an online application business and a security system business. The purpose of this research is to conduct a descriptive study of entrepreneurship in students using technology (Technopreneurship) from all perspectives, including motivation, ownership, managerial, employment, and so on. technology as a basis for entrepreneurship. The results of the discussion found that the use of technology (Technopreneurship) in entrepreneurship can help and develop businesses in the form of making products and in marketing the products, so as to increase business and student income